2006
DOI: 10.1177/1049732305284734
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Medical and Nursing Staff Communication in Nursing Homes: Implications and Insights From Complexity Science

Abstract: Complexity science teaches that relationships among health care providers are key to our understanding of how quality care emerges. The authors sought to compare the effects of differing patterns of medicine-nursing communication on the quality of information flow, cognitive diversity, self-organization, and innovation in nursing homes. Two facilities participated in 6-month case studies using field observations, shadowing, and depth interviews. In one facility, the dominant pattern of communication was a vert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
71
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 28 publications
5
71
0
3
Order By: Relevance
“…This review characterized PSC as problematic with many nursing homes having low scores (indicating poor PSCs), providing further rationale for additional research in this area. As part of this prior literature review (Bonner et al, 2008), and our own literature search, only one empirical study (i.e., Castle & Sonon, 2006) was identified that examined the PSC from the perspective of nursing home top managers. Most of the other studies examined PSC using information coming from nurse aides (Bonner et al, 2008).…”
Section: Patient Safety Culturementioning
confidence: 99%
See 1 more Smart Citation
“…This review characterized PSC as problematic with many nursing homes having low scores (indicating poor PSCs), providing further rationale for additional research in this area. As part of this prior literature review (Bonner et al, 2008), and our own literature search, only one empirical study (i.e., Castle & Sonon, 2006) was identified that examined the PSC from the perspective of nursing home top managers. Most of the other studies examined PSC using information coming from nurse aides (Bonner et al, 2008).…”
Section: Patient Safety Culturementioning
confidence: 99%
“…Most of the other studies examined PSC using information coming from nurse aides (Bonner et al, 2008). Castle and Sonon (2006) examined PSC from the perspective of NHAs. Information came from 425 NHAs, and a hospital PSC instrument was modified for use in nursing homes (i.e., the Hospital Survey on Patient Safety Culture (HSOPSC); Sorra et al, 2007).…”
Section: Patient Safety Culturementioning
confidence: 99%
“…CASs are characterized by a number of agents (staff) interacting locally in a dynamic, non-linear fashion.) Colon-Emeric et al 54 proposed that communication patterns in RAC facilities may influence the quality of care provided to residents. A tolerant and open rather than 'us and them' management style is required to encourage staff uptake of educational programmes.…”
Section: Discussionmentioning
confidence: 99%
“…For managers and administrators, enabling CNA observations within the facility could help unlock the capacity of the CNA to influence depression assessment. Systems developed, however, must attend to the facility barriers to CNA and clinical staff sharing of information (Anderson et al, 2005;Colón-Emeric et al, 2006a;Colón-Emeric et al, 2006b;Piven et al 2006). Given the high CNA turnover, it may argued that the time and cost of further educating CNAs is not prudent; but, providing additional training along with supervisory support may improve CNA morale and job satisfaction, influencing turnover.…”
Section: Discussionmentioning
confidence: 99%
“…No formalized processes are known that permit CNAs to consistently and effectively communicate their accumulated resident observations, influencing the care processes of resident assessment, care planning and decision-making (Colón-Emeric et al, 2006b;Piven et al, 2006). With low Registered Nurse-resident ratios (Eaton, 2000), contact with Registered Nurses and even Licensed Practical or Vocational Nurses may be limited, with few opportunities to share knowledge and jointly solve problems (Colón-Emeric et al, 2006b), much less time for clinical supervision. Positive relationships with nursing staff, especially the MDS Coordinators, improve the likelihood that CNAs will communicate resident observations for more accurate assessment of residents and individualized care planning .…”
Section: Facility and Staff Barriers To Inclusion Of Cna Observationsmentioning
confidence: 99%